Simulation of Hydrogen Purification using Two Bed System Pressure Swing Adsorption - Pratiwi, Vibianti Dwi; Juwari, Juwari; Handogo, Renanto (IPTEK Journal of Proceedings Series, 2017)
Hydrogen has various functions in chemical industries, as an agent of organic compounds synthesis, a reactant in hydrocracking, hydroalkelation, and hydrodesulfurization process in petrochemical industry, a reactant in hydrogenated fat process, a reductant agent in material industry, methanol production, silicon manufacture. Therefore, hydrogen purification is very important process for the industry processes. Pressure Swing Adsorption (PSA) is commonly used hydrogen purification process. Different utility used for hydrogen purification using PSA will change adsorbent’s capacity and pressure to separate the mixture of gas into desirable components. In this study, pressure is varied from 2 to 10 bar and adsorbents are used silica gel and activated carbon. Hydrogen purification using two beds system PSA is simulated using Aspen Adsorption software. Based on the simulation result, it can be concluded that the pressure that gives most steady system is at 7 bar, which produces 99,92 % hydrogen purity using activated carbon in bed 1 and silica gel in bed 2.